Penerapan Metode Analytical Hierarchy Process Dan Tehnique for Order Preference by Similarity to Ideal Solution Dalam Sistem Pendukung Keputusan Penilaian Kinerja Guru - Leni Junika Adrian; Wire Bagye; Mardi Mardi (Journal of Information System Research (JOSH), 2025)
The evaluation of honorary teachers’ performance plays a crucial role in efforts to enhance the quality of education. This study aims to assess the performance of honorary teachers at SMK Negeri 1 Praya Tengah by applying the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The assessment is based on four main criteria—pedagogical, personal, social, and professional competencies—which are further broken down into several sub-criteria. AHP is utilized to determine the weight of each criterion according to its level of importance, while TOPSIS is employed to rank the teachers based on their proximity to the ideal solution. The results show that the teacher labeled A3, Susilawati, S.Pd, achieved the highest preference score of 0,831, making her the top-performing honorary teacher. The combination of these methods provides an objective and measurable evaluation that can serve as a valuable reference for decision-making by the school administration.